Influences of RVG Positions on the Periodic Flow Profiles - Withada Jedsadaratanachai (My University, 2014)
The effects on the positions of rib vortex generators (RVGs) for periodic laminar flow behavior are presented numerically in three-dimensional. The RVGs with constant blockage ratio (b/H, BR = 0.15), the pitch ratio (P/H, PR = 1), and flow attack angle (α=30°) are inserted in isothermal walls of the square channel. The SIMPLE algorithm and the finite volume method (FVM) are applied for the computational domain. The influences of different gap ratios (g/H= 0–0.35) for Reynolds number based on the hydraulic diameter (Dh), Re = 100–1200, are investigated. It is found that the flow profiles can be divided into two parts; the first, similar in flow configuration, but different inu/u0values, is called “periodic flow” and the second, similar in both flow configuration andu/u0values, is called “fully developed periodic flow.” The results reveal that the periodic flow profiles appear around 2nd-3rd modules while the fully developed flow profiles occur around 6th–9th modules. In addition, the periodic flow profiles and fully developed periodic flow profiles become faster in case of the lowest continuous flow area (g/H= 0.20, 0.25, and 0.30) and the regimes close to the RVG.
Keywords: Fluid Dynamics and Turbulent Flows